EL B C G DEBE EMPLEARSE EN MEXICO COMO UNA MEDIDA DE PROFILAXIS DE LA TUBERCULOSIS - LEON, ALBERTO P (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1949)
Laboratory diagnosis of tuberculosis is discussed with special reference to bacteriologic, serologic, hematologic and erythrocyte sedimentation rate technics
REV MEX TUBERCULOSIS
Keywords: MEXICO, MEDIDA, PROFILAXIS, TUBERCULOSIS; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA